Students’ Ability In Reading Comprehension of Recount Text - Permanasari, Pradnya; Awalia, Syaeri Laelatul (Universitas Negeri Padang, 2023)
The purpose of this study was to find out and describe students' ability to read texts, find difficulties faced by students and describe the factors that influence the reading comprehension of class X students of SMK 1 Pemalang in the 2022/2023 academic year in reading comprehension from recount texts. This study used descriptive qualitative method. The results of this study indicate that students' ability to read texts is considered weak at 57.74% (poor). Students' difficulties in reading comprehension of recount texts are seen in terms of mechanical abilities and comprehension. Nearly 50% of the 31 students answered that they did not understand reading comprehension texts. And from the factors faced by students in reading comprehension of recount text factors according to students, physical health can hinder reading, some students answered that they needed to find other learning resources related to reading and comprehension, some students answered that they were interested in reading but there were factors What does not support them in learning to read is environmental factors.